GAMBARAN TINGKAT PENGETAHUAN, SIKAP, DAN TINDAKAN MAHASISWA UNIVERSITAS KRISTEN DUTA WACANA MENGENAI COVID-19 - Yehezkiel Wim Utomo; Ida Ayu Triastuti; Daniel Chriswinanto Adityo Nugroho; Mitra Andini Sigilipoe (Bahasa Indonesia, 2022)
COVID-19 is a new disease that is spreading continuously throughout the world. The government has tried to suppress the rate of spread by providing promotions and education to the public through mass media. The purpose of this research is to find description and relevance with students’ knowledge levels, precautions, and actions regarding COVID-19. This study used a cross-sectional research design using a quantitative approach. This study used primary data, namely filling out a questionnaire involving 108 respondents with inclusion criteria selected using sequential sampling method. The questionnaire consists of respondents' demographics, questions about knowledge, precautions, and actions regarding COVID-19 and uses the spearman rank test to determine the correlation between knowledge of COVID-19, precautions of COVID-19, and preventive actions for COVID-19. Research data showed that most of the respondents had good knowledge of COVID-19 (n = 78), had good precautions of COVID-19(n = 98), and had good preventive actions for COVID-19 (n = 72). There is a significant relevance between knowledge and precautions of COVID-19 (r = 0.301; p = 0.002), knowledge and preventive actions for COVID-19 (r = 0.227; p = 0.018), precautions and preventive action for COVID-19 (r = 0.224; p = 0.011). Respondents already have a good level of knowledge, precautions, and preventive actions for COVID-19. For UKDW students, always obey the health protocols during the COVID-19 pandemic.